Entrepreneurship: Problems and Opportunities for Satoimo Taro Cultivation at Ummul Ayman Islamic Boarding School, Pidie Jaya - Arinal Rahmati; Indrayani Indrayani; Razif Razif (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2023)
This study aims to examine the problems and opportunities of satoimo taro cultivation at the Ummul Ayman Islamic boarding school, Pidie Jaya. This research is a qualitative descriptive study with primary data. The informants in this study were the leaders of the Ummul Ayman Islamic boarding school and students who were engaged in satoimo taro cultivation. The results showed that the problems in satoimo taro cultivation were caused by the inability of good management by the students, narrow product marketing space, lack of product reliability, lack of innovation and creativity, lack of cooperation, lack of government assistance. Meanwhile, in terms of opportunities, this plant has the potential to become an export commodity in China, the vast amount of vacant land within the Ummul Ayman Islamic Boarding School that is provided, as well as the specific time allocation for Islamic boarding school students to grow crops and do entrepreneurship.